MNCS' PERCEPTION ON THE FEASIBILITY OF SOUTH KOREA AS A BUSINESS HUB OF NORTHEAST ASIA - You-Il Lee, (Asian Academy of Management Journal, 2004)
Since the financial crisis of 1997, the South Korean government has moved towards a new market-driven paradigm of economic growth based on foreign direct investment (FDI) replacing the decades old state-driven economic growth model. One of the attempts made by the government is its ambition to transform the nation into a business and economic hub of Northeast Asia. However, despite the growing concern on the topic among government agencies, media, research centers and academia, the absence of a cohesive and realistic approach to the issue is a relative void in the literature. This paper, which is based on findings from interviews with foreign companies operating in Korea during 2002, offers a cultural and institutional insight into the critical and often invisible issues to be considered for a successful realization of the vision.